Talpa altaica Nikolsky 1883 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Talpa altaica Nikolsky 1883 Talpa altaica Nikolsky 1883, Trans. Soc. Nat. St. Petersburg, 14: 165. Type Locality: Russia, Siberia, Altai Mtns, Valley of Tourak. Vernacular Names: Altai Mole. Synonyms: Talpa gusevi (Fetisov 1956); Talpa irkutensis Dybowski 1922; Talpa saianensis Bielovusev 1921; Talpa salairica Egorin 1936; Talpa salairici Corbet 1978; Talpa sibirica Egorin 1937; Talpa suschkini Kastschenko 1905; Talpa tymensis Egorin 1937. Distribution: Taiga zone of Siberia between Ob and Lena Rivers; south to N Mongolia. Conservation: IUCN – Lower Risk (lc). Discussion: Placed by Yudin (1989:52) in genus Asioscalops but see Corbet (1978 c :33). Kratochvíl and Kral (1972) provided karyological evidence for a separation of altaica from the remaining Talpa species. Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Soricomorpha, pp. 220-311 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 307, DOI: 10.5281/zenodo.7316519